If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x+20)=(4x-10)
We move all terms to the left:
(3x+20)-((4x-10))=0
We get rid of parentheses
3x-((4x-10))+20=0
We calculate terms in parentheses: -((4x-10)), so:We get rid of parentheses
(4x-10)
We get rid of parentheses
4x-10
Back to the equation:
-(4x-10)
3x-4x+10+20=0
We add all the numbers together, and all the variables
-1x+30=0
We move all terms containing x to the left, all other terms to the right
-x=-30
x=-30/-1
x=+30
| 2x-x3x-x=-6 | | X*x=30.25 | | 5a+14=-29+14 | | 7(-3+x)=7 | | 6z=49-6 | | -13x+2=-52+23× | | 180=3x+20=4x-10 | | 7/8=y+3/10 | | 2t−t=9 | | 2y+84=6y | | 54/x=12 | | 300-10q=100+6q | | 2x20=x+60 | | 4=2v-8 | | 3=j/14-5 | | 6x+34=88 | | 7q+9=93-3q | | 3=j/4-5 | | -4.2=1.2g | | 9x+4=97 | | 7/2m+12=6+5/2m | | 8x−6x=14 | | 3x+17x-8=4(5x+5) | | -10=7(y-4)+2y | | 14x-86=82 | | 5p+11=3p-19 | | -16=2v+2(v+4) | | 12=15x+7 | | 34=0.5(3x-2-x+6) | | 15=n/8+12 | | 11(w=2)-6 | | 6(x+1)+3(-5x-7)=-9x-15 |